The Roman foundations of the law of nations Alberico Gentili and the justice of empire - Kingsbury, Benedict; Straumann, Benjamin (Oxford : Oxford University Press, 2010)
This text explores ways in which both the theory and the practice of international politics was built upon Roman private and public law foundations on a variety of issues including the organisation and limitation of war, peace settlements embassies, commerce, and shipping.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Gentili, Alberico, -- 1552-1608.; International law -- History; Roman law -- Influence